Condition of vestibular function in patients with Meniere's disease for the early term after treatment - T. A. Shevchenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The efficiency rating of the treatment in patients with Meniere's disease was performed with the help of different methods in accordance to vestibular function for the early term (in 3 months) after treatment. Improvement of clinical course was observed in all groups of patients. However. complex therapy became the most effective method which included pneumomassage of labyrinthine windows and kinesitherapy. The article shows advantages of complex therapy over the medication therapy according to assessment of vestibular dysfunction.